Effects of probiotics on non-alcoholic fatty liver disease: a review of human clinical trials - Cao, Chujin; Shi, Mengxia; Wang, Xiuru; Yao, Ying; Zeng, Rui (Frontiers in Nutrition, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a global public health issue, of which the prevalence is about 25% worldwide. The incidence of NAFLD is increasing in patients with obesity, type 2 diabetes (T2DM) and the metabolic syndrome. The crosstalk between gut microbiota and metabolism-related diseases has been raised great concern. Patients with NAPLD were observed with disruption of gut microbiota. Several researches showed that gut microbiota was the determination in the progression of NAFLD by the experiments using fecal microbiota transplants. The application of probiotics, as one of the most important strategies for the regulation of gut microbiota disorder, have been explored whether it is beneficial to gut-related diseases of intestine-distal organs. Some probiotics were showed to improve the liver parameters and phenotype in patients with NAFLD. The oral intake of them might become the effective management for the prevention and treatment of NAFLD. In this review, we summarized the human clinical trials focusing on the effects of probiotics on NAFLD to give some evidential reference for the administration of NAFLD.